Uses of local ethnic television: Finland Calling (1962–2015) and Michigan’s Upper Peninsula - Pajala Mari (Sage, 2022)
Finland Calling was a bilingual Sunday morning television program targeting Finnish Americans and airing on WLUC-TV, a local commercial station in Michigan’s Upper Peninsula. The show ran from 1962 to 2015, just over 50 years. This article uses it as a case study to argue that if we look beyond prime-time network programming, we can see that US television has not always promoted a homogeneous national culture; rather, it has at times been a resource for the development of distinctive local and ethnic cultures. Based on an analysis of Finland Calling episodes and written sources about the show, the article demonstrates that while the show’s primary target audience was the local Finnish American community, it also resonated with broader conceptions of Upper Peninsula culture, participated in Finnish American cultural activities at the North American level, and emphasized transnational connections between the Upper Peninsula and Finland.